XRD, SEM and petrologic characterization of a L4-L5 ordinary chondrite meteorite - Seixas, T. M.
In this work, a meteorite sample recovered in Morocco is characterized by detailed petrographic observations in transmitted and reflected light optical microscopy and by using XRD and SEM and it is tentatively classified. VIS/NIR spectral analysis of the same meteorite in a previous study suggested that it is seemingly related to the HAMLET meteorite, which was classified as LL4 chondrite. From the obtained results in the refinement of the analysis of the present study, this meteorite is classified as L4 to L5 chondrite. Composition maps across selected chondrules and in the matrix are presented.